«Рум'яна» для небіжчиків (результати досліджень мінеральних артефактів із поховань Золотої Балки) - Нестеровський, В.А.; Дзнеладзе, О.С.; Горбаненко, С.А.; Андрєєв, О.В. (Археологія і давня історія України, 2018)
До наукового обігу введено результати досліджень мінеральних артефактів із поховань
пізньоскіфського могильника Золота Балка. Встановлено, що переважну більшість мінеральної речовини червоно-оранжевого кольору становить реальгар — сульфід арсену. Запропоновано варіант його
використання як певного консерванту для кращого зберігання органічних решток в могилах. The results of the studies of mineral artefacts from
the graves of the Late Scythian burial ground of Zolota
Balka were introduced into scientific circulation.
At this site, 87 graves were excavated; in 10 of them
mineral artefacts were identified. The latter one is the
object of this study, while their significance and role in the funeral rite is the subject.
Analytical studies revealed that the vast majority of the mineral substances of red-orange colour is realgar
(arsenic sulfide). It is a toxic substance with a detrimental effect on the organisms. Its deposits in Ukraine
are unknown. There is an opinion in the archaeological literature that realgar was placed in burials because
of the colour of this mineral. However, a similar colour is inherent in ochre, which is much easier to find in
the surroundings. Taking into account the properties of realgar and given the need to deliver it from afar, we
consider that it was used as a preservative for better storage of organic remains in the graves and for less reproduction
of pathogenic flora within the family crypts, where later the dead would be buried again.